THE USE OF ONLINE WEB-BASED SOFTWARE I-TREE CANOPY AS AN ALTERNATIVE IN SUPPORTING COMMUNITY BASED ZERO DELTA Q PLANNING - Raharjo, Akhmadi Puguh (Badan Pengkajian dan Penerapan Teknologi (BPPT), 2018)
Zero Delta Q is a policy to ensure that any additional surface runoff due to development does not further burden the drainage or river system. In case of Zero Delta Q application planning at the community level, a software is needed that can help classify and quantify the existing land cover class in area where the community is located. The purpose of this study is to look at the time needed and reliability of the i-Tree Canopy web-based software online in classifying and quantifying land cover classes on one of the sub-catchments in the Pesanggrahan River Basin. The land cover class is divided into six: trees, grasses / undergrowth plants, open area, water bodies, pavement / road and roof of the building. For comparison, an RBI map is used from the same area to see the extent of each class of land cover. Observation of each point requires an average time of 5.2 ± 1.0 seconds. The difference between direct sub-basin measurements using i-Tree Canopy and detailed analysis results from the RBI map is within the range of 0.41% or 0.36 Ha for each individual class of land cover. For a relatively small study area (under 100 ha) and when supported with reliable internet access, this web-based online software is sufficiently reliable in assisting the application planning process to support Zero Delta Q policy.